Pedoman umum penyusunan peraturan daerah pengelolaan hutan - Patlis, J.M. (Center for International Forestry Research, 2004)
Indonesia has experienced a rapid change in governance since the fall of President Suharto, with a profound shift to regional autonomy and decentralised management that rests primarily with the 420 or so districts (kabupaten) and municipalities (kota) in the country. In exercising this new authority, district/municipal governments maintain significant responsibilities and obligations. Districts/municipalities have a responsibility to ensure that their laws and policies are consistent with those of the central government. They also have a responsibility to develop laws in the public interest and to follow the principles of what is typically considered ‘good governance’, in order to ensure that natural resources are sustainably used. While recent legislation often uses broad, general language to refer to the three pillars of good governance—access to information, participation, and justice—there remain few meaningful details on how regional governments are to implement those principles in real-life situations. In addition, there is generally no consistent methodology used in developing new laws. This paper provides a rough guide for developing regional legislation to manage forestry resources. It first describes the responsibilities of regional governments. Next, it describes some of the more important principles that should be applied in lawmaking and identifies some feasible alternatives to implement them. It then outlines a methodology for developing new legislation. The paper proposes alternatives and methodologies that a district/municipality with limited experience and limited funding can carry out for meaningful improvement in development of new legislation for forestry management.